A facile approach of light driven nanoassembly for the controlled accommodation of doxorubicin. (29th June 2017) - Kollarigowda, Ravichandran H; Mathews, Anu Stella; Abraham, Sinoj; Montemagno, Carlo D
Abstract: Fabrication of biodegradable polymer nanoparticles (NPs) is a fascinating research area because of their great potential in biomedical applications. In this work, apart from the well-reported di- or tri-block copolymer nanoassembly, homopolymers based on poly(caprolactone) were designed, synthesized and fabricated to obtain 200 nm size NPs, controlled by the duration of the ultraviolet (UV) cross-linking process. Furthermore, the encapsulated drug, doxorubicin, and the cross-linked NP system were produced via a UV cross-linking micro-emulsion process. Importantly, the drug-encapsulated NPs were taken up intracellularly and cytotoxicity studies were carried out in two different cell lines, HUVEC and SK-OV-3. The NP system reported here is a complimentary approach to existing therapeutic agents in biomedical engineering based on the straightforward utility of a single UV cross-linkable polymer with the ability to encapsulate and release drugs. It holds the promise of fine-tuning nano carriers for the targeted release of therapeutic moieties or growth factors, expanding the possibilities of tissue engineering.